2016
DOI: 10.1002/jmri.25171
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal function using intravoxel incoherent motion diffusion‐weighted imaging and dynamic contrast‐enhanced MRI

Abstract: Objective To assess the correlation between each of intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and dynamic contrast-enhanced MRI (DCE-MRI) metrics in renal parenchyma with renal function, in a cohort of patients with chronic liver disease. Materials and Methods Thirty patients with liver disease underwent abdominal MRI at 1.5T, including a respiratory-triggered IVIM-DWI sequence and a coronal 3D FLASH DCE-MRI acquisition. Diffusion signals in the renal cortex and medulla were fitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 28 publications
5
34
1
Order By: Relevance
“…DWI is a powerful MRI technique used for imaging molecular movement or diffusion that reflects changes in microstructure of biological tissues . Previous studies have confirmed that IVIM‐DWI can be used to assess renal function . However, renal pathology plays an important role in guiding therapy and follow‐up of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI is a powerful MRI technique used for imaging molecular movement or diffusion that reflects changes in microstructure of biological tissues . Previous studies have confirmed that IVIM‐DWI can be used to assess renal function . However, renal pathology plays an important role in guiding therapy and follow‐up of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Previous studies have confirmed that IVIM-DWI can be used to assess renal function. 13,14,[28][29][30][31] However, renal pathology plays an important role in guiding therapy and follow-up of CKD patients. We applied IVIM-DWI to evaluate alterations of renal function and pathology, especially in patients of CKD stage 1 (with normal or high eGFR) in various renal diseases, which may lead to chronic renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although perfusion parameters can be acquired from IVIM models, they are weakly correlated with the parameters derived from DCE‐MRI, such as the GFR and the mean transit time (MTT). Therefore, when assessing perfusion, these two methods are complementary . In addition, compared with the monoexponential model, the three‐parameter model reaches a more precise fit to the diffusion signal decay.…”
Section: Renal Fmrimentioning
confidence: 99%
“…Similar results were found in patients with acute UUO 36 , by comparing DWI before and after removal of UUO. While all the above studies indicate that DWI-measured diffusion coefficient is associated with renal functional impairment, good correlation was not detected between the DWI parameters and contrast-enhanced MRI measured GFR and RPF 48 . This discouraging result could be due to high estimation errors of the parameters, or as the authors suggested that water diffusion is more independent of GFR or RPF than we imagine.…”
Section: Non-contrast Mrimentioning
confidence: 80%